Neuroendocrine tumor incidentally detected during living donor - Akbulut, S; Isik, B; Cicek, E; Samdanci, E; Yilmaz, S (2018)
To our best knowledge, no case of a tumor that was incidentally detected during living donor hepatectomy (LDH) has been reported in the English language medical literature. We present two cases in which grade. neuroendocrine tumors (NET) were incidentally detected during our twelve-year LDH experience. First Case: A 26-year-old male underwent LDH for his brother suffering from HBV-related chronic liver disease (CLD). After right lobe LDH, intestinal length was measured as part of a study concerning the relationship between small intestinal lengths and surgical procedure. At this stage, a mass lesion with a size of 10 mm x 10 mm was detected on the antimesenteric surface, approximately 90 cm proximal to the ileocecal valve. A wedge resection with primary intestinal anastomosis was performed. Second Case: A 29-year-old male underwent right lobe LDH for his father with hepatitis B virus (HBV)-related CLD. An abdominal exploration immediately prior to the closure of the incision revealed that the appendix vermiformis was edematous and had firmness with a size of 8-10 mm at its tip. An appendectomy was performed. The pathological examinations of the specimens of both patients revealed grade 1 NET. In conclusion, even if patients undergoing LDH are healthy individuals, whole abdominal cavity should be gently palpated and all findings recorded after completing laparotomy. Suspected masses or lesions should be confirmed by frozen section examination. Such an approach would avert potential medicolegal issues. (c) The Author(s) 2018. Published by Baishideng Publishing Group Inc. All rights reserved. C1 [Akbulut, Sami; Isik, Burak; Cicek, Egemen; Yilmaz, Sezai] Inonu Univ, Fac Med, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Akbulut, Sami; Isik, Burak; Yilmaz, Sezai] Inonu Univ, Fac Med, Liver Transplant Inst, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Samdanci, Emine] Inonu Univ, Fac Med, Dept Pathol, TR-44280 Malatya, Turkey.